Development of a Hybrid Quantum Key Distribution Concept for Multi-User Networks - Y, Begimbayeva; T, Zhaxalykov; M, Makarov; O, Ussatova; S, Tynymbayev; Zh, Temirbekova (International journal of advanced computer science & applications, 2024)
This paper investigates the increasing concerns related to the vulnerability of contemporary security solutions in the face of quantum-based attacks, which pose significant challenges to existing cryptographic methods. Most current Quantum Key Distribution (QKD) protocols are designed with a focus on point-to-point communication, limiting their application in broader network environments where multiple users need to exchange information securely. To address this limitation, a thorough analysis of twin-field-based algorithms is conducted, emphasizing their distinct characteristics and evaluating their performance in practical scenarios in Sections II, III, and IV. By synthesizing insights from these analyses, integrating cutting-edge advancements in Quantum Communication technologies, and drawing on proven methodologies from established point-to-point protocols, this study introduces a novel concept for a Hybrid Twin-Field QKD protocol in Section IV. This network-oriented approach is designed to facilitate secure communication in networks involving multiple users, offering a practical and scalable solution. The proposed protocol aims to reduce resource consumption while maintaining high-security standards, thereby making it a viable option for real-world quantum communication networks. This work contributes to the development of more resilient and efficient quantum networks capable of withstanding future quantum-based threats.